PENDAMPINGAN PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN BAGI GURU TAMAN KANAK-KANAK - Margiana Dewi Maria Madonna Maran; Yoakim Yolanda Mario Leu (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
The pedagogical competence of kindergarten teachers is crucial in forming the foundation of child development, yet educators in East Nusa Tenggara still face challenges in developing systematic learning tools. The focus of this activity was to provide intensive mentoring for 15 teachers to improve their skills in developing creative and innovative Lesson Implementation Plans (RPP) in accordance with the Independent Curriculum. The activity was conducted online through interactive lectures, Q&A sessions, demonstrations of the development process, simulations, and independent work practice, culminating in an in-depth evaluation. The results of the activity demonstrated a significant increase in teachers' professional capacity as reflective learning designers. Based on technical evaluation data, 95% of participants understood and were able to implement the RPP development very well, while the remaining 5% required additional guidance related to the integration of learning outcomes with child development assessment instruments. These findings demonstrate that the play-while-learning strategy incorporated into the learning design is highly effective in optimizing students' cognitive, physical-motor, and social-emotional aspects. The main conclusion emphasized that ongoing mentoring through non-formal workshops is a strategic necessity to ensure a structured and detailed learning process. With a thorough mastery of learning design, teachers can carry out their roles professionally to realize a more meaningful and measurable quality of early childhood education in the midst of a global era that continues to experience rapid development. ABSTRAK Kompetensi pedagogik guru Taman Kanak-Kanak sangat krusial dalam membentuk fondasi perkembangan anak, namun pendidik di Nusa Tenggara Timur masih mengalami hambatan dalam menyusun perangkat pembelajaran sistematis. Fokus kegiatan ini adalah memberikan pendampingan intensif bagi 15 guru guna meningkatkan kecakapan mereka dalam menyusun Rencana Pelaksanaan Pembelajaran (RPP) kreatif dan inovatif sesuai Kurikulum Merdeka. Tahapan kegiatan dilaksanakan secara daring melalui metode ceramah interaktif, tanya jawab, demonstrasi alur penyusunan, simulasi, hingga praktik kerja mandiri yang diakhiri dengan evaluasi mendalam. Hasil kegiatan menunjukkan peningkatan signifikan pada kapasitas profesionalisme guru sebagai perancang pembelajaran reflektif. Berdasarkan data evaluasi teknis, tercatat bahwa 95% peserta telah memahami serta mampu mengimplementasikan penyusunan RPP dengan sangat baik, sementara 5% sisanya memerlukan bimbingan tambahan terkait integrasi capaian pembelajaran dengan instrumen asesmen perkembangan anak. Temuan ini membuktikan bahwa strategi bermain sambil belajar yang tertuang dalam desain pembelajaran sangat efektif dalam mengoptimalkan aspek kognitif, fisik motorik, serta sosial-emosional peserta didik. Simpulan utama menegaskan bahwa pendampingan berkelanjutan melalui lokakarya non-formal menjadi keharusan strategis untuk memastikan proses pembelajaran yang terstruktur dan terperinci. Dengan penguasaan desain pembelajaran yang matang, guru dapat menjalankan perannya secara profesional demi mewujudkan kualitas pendidikan anak usia dini yang lebih bermakna dan terukur di tengah era global yang terus mengalami perkembangan pesat.